STRATEGIC PLANNING OF HOSPITALITY INFORMATION SYSTEMS USING THE WARD AND PEPPARD APPROACH CASE STUDY AT BULEUD VILLA, GARUT DISTRICT - Rosliani, Elin; Rahayu, Dinar (RISTEC : Research in Information Systems and Technology, 2022)
Hospitality is one area that has the potentia l to implement information systems because hospitality is a business that prioritizes satisfaction, in this case, namely service. A good business stra tegy is needed to support the business. Ta lking about business stra tegy will not be separated from the so-called strategy of information systems and information technology. Therefore, a mature information system strategic planning can be used as a reference to ga in a competitive advantage for Villa Buleud Garut. The purpose of this study is to ana lyze environmental factors to determine the strengths, weaknesses, opportunities and threats that are owned and to identify the critical success factors so that a proposed information system strategy plan can be developed in the form of an application development portfolio at the future Villa Buleud. In this study the authors made direct observations at Villa Buleud, conducted interviews, and gave questionnaires to related parties and read literature. In compiling the framework in this study the authors used the Wa rd and Peppa rd approach. Which of these approaches is to carry out an analysis of the Internal Business Environment, Externa l Business Environment, Interna l IS/IT Environment, and Externa l IS/IT Environment using severa l ana lytica l methods, namely Va lue Chain ana lysis, PEST Analysis, Five Force Porter, McFarlan Strategic Grid, SWOT Ana lysis, Critical Success Factor, and Ba lanced Scoreca rd. The fina l result of this resea rch is the proposed formulation of the future IS/IT stra tegy for Villa Buleud Ga rut which includes changes to the vision and mission of Villa Buleud, changes to organizationa l structure, information system application requirements, network architecture, future business processes, and future Villa Buleud application portfolio. Keywords: Information Systems and Information Technology Strategy, Wa rd and Peppard, Va lue Chain ana lysis, PEST Ana lysis, Porter's Five Forces, McFarla n Strategic Grid, SWOT Ana lysis, Critical Success Factor, Balanced Scorecard, and application portfolio